Costumes religieux RELIGIOUS CLOTHING costumes habit historical... - Etienne Mahler (Wikimedia Commons, 2014)
Notice visuelle issue de Wikimedia Commons pour la demo du fonds documentaire.
Droits : Licence Creative Commons Zero, Public Domain Dedication via Wikimedia Commons
Keywords: histoire; iconographie; gravure; photographie; wikimedia commons; Iconographie